Integrated experimental and computational investigations to evaluate the anticancer potential of Benzenethiol-derived Schiff Base ligand and its Cu(II), Co(II), Ni(II) and Zn(II) complexes - Gowda, Bhavana G.; Singh, Pallavi; Kumari, Pallavi; Sienkiewicz, Jozef E.; Jasik, Patryk; Kaygili, Omer; Kollur, Shiva Prasad (Elsevier Science Sa, 2026)
A Schiff base ligand derived from benzenethiol and bearing multiple donor sites was synthesized via a single-step condensation process. This ligand was then used to prepare a series of comparative Cobalt(II), Copper(II), Nickel (II) and Zinc(II) coordination compounds. The significance of this study lies in its integration of synthesis, multitechnique structural verification, biological testing, and quantum-chemical interpretation within a coherent framework. This approach enables the establishment of structure-property-activity relationships rather than merely reporting isolated observations. The ligand and its metal complexes were characterized using Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, ultraviolet-visible spectroscopy, mass spectrometry and elemental analysis. These techniques supported the formation of coordination bonds through the azomethine nitrogen, amino nitrogen and thiol sulfur atoms. Anticancer potential was evaluated in human glioblastoma and normal fibroblast cells to assess selectivity. The free ligand and the copper(II) and nickel (II) complexes exhibited the greatest activity, demonstrating low half-maximal inhibitory concentration values and selective toxicity toward cancer cells. Fluorescent staining with rhodamine-123 indicated disruption of mitochondrial function, consistent with an apoptosis-related mechanism. Density functional theory and timedependent density functional theory calculations, together with vibrational assignments, electronic transition analysis, density of states evaluation and electron localization function mapping, explain how metal coordination modulates bonding, electronic structure and optical response across the series. Overall, this integrated experimental-computational approach identifies the benzenethiol Schiff base platform as a promising scaffold for developing selective, metal-based anticancer agents, and provides a basis for future optimization through targeted structural modification and expanded biological evaluation.
Keywords: Schiff base ligand; Metal complex; Cytotoxicity; Electron localization function